Uma cartografia intelectual e cultural da Europa em Fernando Pessoa - Steffen Dix (Ler História, 2025)
Until now, Fernando Pessoa’s role as a European thinker has never been dealt with in detail. This concerns both the way he looked at the Europe of his time, as well as some of his notions that are surprisingly up-to-date. This gap is striking, given that Pessoa was always attentive to European modernity. Although it was still quite fragmentary, Pessoa outlined the notion of a European cosmopolitanism, which became the centre of sociological and political debates only later and was mainly based on texts by Ulrich Beck. Therefore, the main purpose of this article is to analyse these two points in more detail, emphasising that Pessoa was in fact one of the most European writers of the 20th century.